The use of InCaS model to identification and measuring of structural capital in small and medium enterprises = Wykorzystanie koncepcji INCaS do identyfikacji i pomiaru kapitału strukturalnego w małych i średnich przedsiębiorstwach - Szczepankiewicz, Elżbieta Izabela (Zielona Góra: Faculty of Economics and Management Press)
Structural resources are an important component of the market value of many business entities. For many years attempts have been made at developing uniform methods and models for identification and valuation of structural capital. "Intellectual Capital Statement - Made in Europe" (InCaS) that constitutes a particularly useful, complex tool to assess, to report and to develop the intellectual capital and structural capital of an modern SME companies.
Keywords: zasoby strukturalne; kapitał strukturalny; kapitał intelektualny; structural resources; structural capital; Intellectual capital